2007
DOI: 10.1113/jphysiol.2007.128447
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of multisegmental monosynaptic responses in a variety of leg muscles during walking and running in humans

Abstract: Motor responses evoked by stimulating the spinal cord percutaneously between the T11 and T12 spinous processes were studied in eight human subjects during walking and running. Stimulation elicited responses bilaterally in the biceps femoris, vastus lateralis, rectus femoris, medial gastrocnemius, soleus, tibialis anterior, extensor digitorum brevis and flexor digitorum brevis. The evoked responses were consistent with activation of Ia afferent fibres through monosynaptic neural circuits since they were inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
166
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(188 citation statements)
references
References 70 publications
20
166
0
2
Order By: Relevance
“…8A, left traces), and the modulation of monosynaptic reflex responses. Courtine et al (2007b) observed similar modulation pattern of monosynaptic reflex responses from lower limb muscles during human locomotion (Fig. 8B).…”
Section: Neurophysiological Plasticity In Response To Trainingsupporting
confidence: 72%
See 1 more Smart Citation
“…8A, left traces), and the modulation of monosynaptic reflex responses. Courtine et al (2007b) observed similar modulation pattern of monosynaptic reflex responses from lower limb muscles during human locomotion (Fig. 8B).…”
Section: Neurophysiological Plasticity In Response To Trainingsupporting
confidence: 72%
“…In fact, state-dependent processing of sensory input has been demonstrated in humans as well. Courtine et al (2007b) showed that the gain in the monosynaptic neural pathway is modulated in virtually all lower limb muscles of normal subjects during walking in a manner similar to the patterns observed in the bipedally walking rat (Fig. 8B) .…”
Section: Are the Variations In The Pathways Activated From Step To Stsupporting
confidence: 68%
“…1 Recently, T11-12 stimulation has been reported to induce multisegmental monosynaptic responses in lower limb muscles in healthy subjects. [2][3][4] These responses have been recorded in both lower limbs. However, no studies have been published on the response to T11-12 electrical stimulation of the upper limbs in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…8 These multisegmental responses could also be useful in testing physiological function and circuitries between the upper and lower limbs, as related to the spinal cord. 2,3 The purpose of this electromyographic study is to compare the multisegmental muscular responses of upper and lower limb muscles with electrical stimulation of T11-12 spinal segment in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation